Perangkat Pembelajaran Ekonomi Berbasis Literasi Informasi Untuk Kelas X SMA Negeri 8 Bone - Wahidayanti, Wahidayanti; Herman, Herman; Inanna, Inanna (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
The study aims at examining (i) the quality (valid,practical, and effective) of econmic learning tools based on literacy which had been developed, (ii) the students’ response after being taugh by using economic learning tools based on literacy. The study was development research (Research and Development) which employed Thiagarajan and Sammen (Four-D) model which consisted of four stages, namely (1) define, (2) design, (3) development, and (4) dissimination. The test of learning tools was conducted to grade X student at SMAN 8 Bone of academic year 2018/2019. Data were collected using observation sheet, learning test, and questionnaire. Data were then analysed using descriptive analysis technique. The results of the development of economic learning tools based on literacy which cover the lesson plan, the students’ worksheet, learning test indicated that  (1) the economic learning tools based on literacy which had been developed produce a valid, practical, and effective learning tools, (2) the students’ response after being based taught using economic learning tools based on literacy is positive. The conclusion which had been developed can improve learning outcomes on the lesson material of problems of economic and economic system